Secularism - An Impractical Idea - Shah, Govinda K. (Bodhi: An Interdisciplinary Journal, 2019)
The article explores the various meanings and concepts of secularism presented by famous ideologues and sociologists of their time. Two contrary concepts of the secularism - one that defines secularism as denial of existence of religions or supernatural forces and another that defines secularism as concept of peaceful co-existence and mutual harmony has been discussed here. The difference of application of secularism on the individual human being and a state is also explained here. The article concludes that no state of human being can remain isolated or indifferent from the influence of religion even if they want. None of the concepts of secularism apply in real life performances; neither on individual nor state.